Muscle tone, stiffness, and elasticity in elite female cyclists after consecutive short competitions - Rotllan, C.; Corbi, F.; Viscor, G. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In professional road cyclists, most overload injuries affect the lower limbs and are mostly represented by contractures or muscle shortening, characterised by a variation of muscular tone, stiffness, and elasticity. This real-life study aimed to assess specific mechanical parameters in top-class female cyclists who participated in 3 races a week. METHODS: Six professional cyclists were evaluated. This pilot study consisted of a controlled trial and three days of competition, with rest days between them. MyotonPRO was used to measure tone, stiffness, and elasticity in six leg muscles: vastus lateralis (VL), vastus medialis (VM), rectus femoris (RF), biceps femoris (BF), lateral gastrocnemius (LG) and medial gastrocnemius (MG). Daily basal and pre- and post-race measures were carried through to the 3 races in a week. RESULTS: The muscular tone of VL, VM, LG, and MG and the stiffness of VL, VM, RF, BF, LG, and MG decreased after races. VL and RF were mostly affected (p = 0.05) and (p = 0.009), respectively. Basal elasticity improved over time until the last day. CONCLUSION: Muscle tone and stiffness decreased after a very intense and exhausting cycling endurance competition. Basal elasticity improved immediately after the race and continued this trend until the end of the week. Two aspects could affect muscle properties during competition; stress factor before and during competition and post-competition neuromuscular fatigue.